2005
DOI: 10.1007/s00125-005-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the association of the GNB3 825C>T polymorphism with components of the metabolic syndrome in white Danes

Abstract: Aims/hypothesis: The 825C>T polymorphism in the gene encoding the G protein β3 subunit (GNB3) causes enhanced G protein activation and increased in vitro cell proliferation. This polymorphism is also repeatedly associated with an increased risk of hypertension and has been studied in relation to obesity with divergent results. Only a few association studies have investigated whether this polymorphism is related to type 2 diabetes or the metabolic syndrome. We estimated the impact of the GNB3 825C>T polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 53 publications
4
29
2
Order By: Relevance
“…In this study, single locus analyses did not show significant main effects of GNB3 rs5443 (in either genotypic test or odds ratio analysis) on the risk of obesity or overweight in the subjects. Our results were in agreement with those of several other studies (Andersen et al 2006;Hayakawa et al 2007;Suwazono et al 2004). A previous study by Andersen et al (2006) suggested that there is no major involvement of the GNB3 rs5443 polymorphism in obesity in white Danish subjects.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, single locus analyses did not show significant main effects of GNB3 rs5443 (in either genotypic test or odds ratio analysis) on the risk of obesity or overweight in the subjects. Our results were in agreement with those of several other studies (Andersen et al 2006;Hayakawa et al 2007;Suwazono et al 2004). A previous study by Andersen et al (2006) suggested that there is no major involvement of the GNB3 rs5443 polymorphism in obesity in white Danish subjects.…”
Section: Discussionsupporting
confidence: 94%
“…Our results were in agreement with those of several other studies (Andersen et al 2006;Hayakawa et al 2007;Suwazono et al 2004). A previous study by Andersen et al (2006) suggested that there is no major involvement of the GNB3 rs5443 polymorphism in obesity in white Danish subjects. Hayakawa et al (2007) also demonstrated that the GNB3 rs5443 polymorphism is unlikely to influence obesity in Japanese subjects who underwent general health examinations.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Biochemical, anthropometric and physiological measurements These analyses were performed as previously described [22].…”
Section: Subjects and Materialsmentioning
confidence: 99%